2012
DOI: 10.1111/j.1754-4505.2012.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient satisfaction, quality of life, and bite force between elderly edentulous patients wearing mandibular two implant‐supported overdentures and conventional complete dentures after 4 years

Abstract: This study compared two groups of patients who were elderly and edentulous, one group included subjects who had mandibular overdentures supported by two implants (Group I); the other groups wore conventional complete dentures (Group II). This retrospective study included 100 edentulous patients (50 from each group) with an average age of 67.86 years, who had been followed for 4 years. The groups were compared in terms of patient satisfaction, quality of life (QOL), and bite force. The bite force and patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 34 publications
2
47
1
6
Order By: Relevance
“…They have also been found to be more gratifying for edentulous patients than a mandibular complete denture . The placement of two interforaminal implants and the use of abutments to retain the denture increases stability and improves the biting force of the mandibular overdenture compared to conventional denture wearers …”
Section: Discussionmentioning
confidence: 99%
“…They have also been found to be more gratifying for edentulous patients than a mandibular complete denture . The placement of two interforaminal implants and the use of abutments to retain the denture increases stability and improves the biting force of the mandibular overdenture compared to conventional denture wearers …”
Section: Discussionmentioning
confidence: 99%
“…The mean of the left-and right-side values was considered as one value. [19] The maximum biting force was measured at baseline (i.e., 1 month after conventional denture insertion) and at 3, 6, and 12 months intervals after implant loading.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…Attachment to the implants improves stability and function of the prostheses and increases patient satisfaction . The implant connection also improves neuromuscular activity and adaptation and thereby substantially improves masticatory function in edentulous patients . In addition, it has been shown that those with implant treatment can achieve nearly double maximum forces compared with those who have conventional dentures …”
Section: Introductionmentioning
confidence: 99%